ANALYSIS OF THE EFFECT OF CAPITAL RATIO, ASSET QUALITY, EARNING, LIQUIDITY, AND SENSITIVITY TO MARKET RISK ON BANKING FINANCIAL PERFORMANCE REGISTERED IN INDONESIA STOCK EXCHANGE - Simbolon, Novi Handayani (Asosiasi Dosen Akuntansi Indonesia, 2020)
This research was conducted with the aim of testing and analysing the effect of Capital, Asset Quality, Earning, Liquidity, and Sensitivity To Market Risk ratios which are proxied by financial ratios of Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), Net Interest Margin (NIM), Operating Expenses Operating Income (OEOI or BOPO), Loan To Deposit Ratio (LDR), and Interest Rate Risk (IRR) on the financial performance of banks listed on the Indonesia Stock Exchange which is proxied by the financial ratio of Return on Assets (ROA). The population in this study were all banking companies listed on the Indonesia Stock Exchange in the period 2008 to 2018 of 22 banks and made the entire population a research sample, so that the number of observations in the study was 242 observations. Data is processed and tested through panel data regression using Eviews statistical test equipment. The results obtained in this study indicate that CAR, NPL, NIM, OEOI, LDR, and IRR simultaneously have a significant effect on ROA, whereas partially it is known that CAR and NIM have significant positive effect on ROA, NPL and OEOI significantly negative effect on ROA, LDR does not have a significant negative effect on ROA, and finally IRR has no significant positive effect on ROA.